Functional biomedical hydrogels for in vivo imaging. Issue 48 (29th November 2016) - Lei, Kewen; Ma, Qian; Yu, Lin; Ding, Jiandong
Abstract : In vivo imaging of biomedical hydrogels enables real-time and non-invasive visualization of the status of structure and function of hydrogels. Abstract : Hydrogels have gained tremendous attention owing to their great potential in biomedical applications such as tissue engineering and drug delivery. Their in vivo fate like in vivo degradation serves as a crucial factor in achieving the desired efficacy. Traditional anatomic observation has been used to investigate the in vivo degradation of hydrogels; however, invasive assessment at each time point significantly increases the number of animals needed for each experiment and is not able to monitor the same formulation throughout the whole period. In recent years, hydrogels functionalized with contrast agents have emerged as a non-invasive tool for long term in vivo tracking of the degradation patterns of hydrogel systems, enabling spatial and temporal visualization of the status of structure (morphology, volume, porosity, etc. ) and function (cell distribution, foreign response, etc. ) of implanted hydrogels. In this review, current mainstreams of functional imaging hydrogels for in vivo tracking and their synthetic strategies are summarized and discussed. The future of functional imaging hydrogels is also envisioned based on the recent advances in imaging techniques.